Programas e políticas públicas para o desenvolvimento de vínculos de negócios entre grandes empresas compradoras e pequenos fornecedores locais - Bourguignon, Milber Fernandes Morais (2008)
Business linkages are characterized as relationships between large companies and small local suppliers, with benefits such as business increase among companies, costs reduction, and increase of the local economy with direct implications to the region development. It makes the State possibly interested in those linkages, having public policies as action tools. The objective of this dissertation is to identify conditions under the State may establish public policies to promote such linkages. In the bibliographic an analysis of themes related to the relationship between companies, as well as of the Brazilian investment environment is made. Two concepts are also analyzed: business linkages and public policies. To reach the research objective two programs were studied, both with the objective of fostering the business relationship between big buyers and small suppliers: Projeto Vínculos and Programa de Desenvolvimento de Fornecedores (carried out in the Brazilian states of Maranhão, Espírito Santo, and Pará). Fourteen members of organizations related to the theme, who authorized the transcription for further analysis, were interviewed. The final conclusion indicates that the State may stimulate the development of business linkages through public policies under the following conditions: as complementation of State policies, as professional qualification policies, as investments attraction complementation, as a policy to promote the technology transfer, and as a policy to the development ofthe business environment.